MARKETING COMMUNICATION OF COFFEE SHOP STRATEGY IN MAINTAINING SALES IN THE NEW NORMAL ERA OF COVID-19: CASE STUDY OF KOPI KENANGAN COMPANY IN SURABAYA - Fuad, Andi Muhammad; Dharmawan, Awang (The Commercium, 2022)
The marketing communication strategy on Kopi Kenangan when Covid was able to maintain sales. The realization of the marketing communication strategy itself is carried out by Kopi Kenangan using a 3P marketing mix strategy, namely product, price, and promotion. The product innovation by Kopi Kenangan is one of the most prominent marketing communication strategies. With several product innovations, Kopi Kenangan managed to maintain sales in the midst of the pandemic and the new normal.This research uses a case study research method with descriptive qualitative type, because this research only describes situations or events. By using interview and observation techniques, data were taken from several informants, namely Kopi Kenangan managers, employees, and consumers.